2016
DOI: 10.18632/oncotarget.14271
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative plasma glypican-3 level may enable prediction of the risk of recurrence after surgery in patients with stage I hepatocellular carcinoma

Abstract: Glypican-3 (GPC3) is a glycosylphosphatidylinositol-anchored cell surface protein overexpressed in hepatocellular carcinoma(HCC), and its overexpression is associated with poor prognosis. The diagnostic potential of GPC3 as a serum marker has been reported. In the present study, we evaluated the usefulness of plasma GPC3 as a predictor for recurrence after surgical resection in stage I HCC patients by newly developed an enzyme-linked immunosorbent assay (ELISA) system. Current study demonstrated that high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…It was recently reported that GPC3-expression level serves as a predictive marker and improves diagnostic efficacy when used with other tumor markers in adults with HCC. 40,41 In this study, GPC3 levels decreased temporarily at least once in cases 2, 3, 5, 6, 7, 11, and 13 during the follow-up period. Furthermore, two patients (cases 2 and 13) who maintained low GPC3 levels received comparatively good prognoses, suggesting that circulating GPC3 level might also serve as a predictive marker of GPC3-peptide-vaccine efficacy for the treatment of pediatric solid tumors.…”
Section: Discussionsupporting
confidence: 50%
“…It was recently reported that GPC3-expression level serves as a predictive marker and improves diagnostic efficacy when used with other tumor markers in adults with HCC. 40,41 In this study, GPC3 levels decreased temporarily at least once in cases 2, 3, 5, 6, 7, 11, and 13 during the follow-up period. Furthermore, two patients (cases 2 and 13) who maintained low GPC3 levels received comparatively good prognoses, suggesting that circulating GPC3 level might also serve as a predictive marker of GPC3-peptide-vaccine efficacy for the treatment of pediatric solid tumors.…”
Section: Discussionsupporting
confidence: 50%
“…22 It was recently reported that the level of GPC3 also serves as a predictive marker and improves diagnostic efficacy when used with other routine parameters in HCC. 23,24 Therefore, we evaluated the level of these tumor markers before and after vaccinations and their utility in GPC3 peptide vaccine therapy. GPC3 levels were detectable in the plasma of all patients before vaccination; these decreased temporarily at least once in Patients 1, 5, 6, 7, 8, 9, 10, and 11 during the follow-up period (8/11 patients, 72.7%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lots of tissue microarray and immunohistochemical data showed that GPC3 is highly expressed in more than 70% of HCC samples, but not in normal liver tissues, benign liver lesions, liver cirrhosis or hepatitis tissues [5,[63][64][65]. Also, the expression level of GPC3 is correlated with prognosis [66][67][68][69]. In addition, GPC3 is also highly expressed in some other cancers such as hepatoblastoma [70], lung squamous cell carcinoma [71], ovarian yolk sac tumor [72], melanoma [73], and urothelial carcinoma [74].…”
Section: Gpc3 As a Target For Clinical Diagnosis And Its Significancementioning
confidence: 99%